PENGARUH SUHU DAN VOLUME AIR PADA DESTILASI PENYULINGAN MINYAK ATSIRI TIPE UAP DAN AIR PADA TANAMAN SIRIH HIJAU (Piper betle L.) (The Effect of Water Temperature and Volume on Distillation of Essential Oil, Using Steam and Water Type Green Betel Plant ( - Putri Azzahra; Achwil Putra Munir; Taufik Rizaldi (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT   Betel is a terna plant or a kind of spice plant. Green betel plant (Piper betle L.) included in the family Piperaceae. The betel plant contains a volatile oil which has a typical smell, volatile at room temperature without any decomposition.. The objective of this research was to find  the best temperature and volume of water in distillation of volatile oil using steam and water type in green betel plant (Piper betle L.). This research used experimental design method of completely randomized design with 2 the factors consisting of 3 levels with 3 replicates i.e heating temperature with temperatures of 94˚C, 98˚C, and 102˚C and water volume of 30 liters, 35 liters, and 40 liters. Parameters observed were yield, solubility in alcohol and color. From results of the research, it was found that the average of best oil yield was from combination of temperature treatment of 98˚C and water volume of 40 liters that was 0,143%. The color of betel oil was yellow-red and solubility in alcohol was 90% at 1:1,9.  Keywords : Essential oil, Piper betle, Yield. ABSTRAK   Sirih merupakan tanaman terna atau sejenis tanaman rempah. Daun sirih hijau (Piper betle L.) termasuk dalam familia Piperaceae. Tanaman sirih mengandung minyak atsiri yang merupakan masa berbau khas, mudah menguap pada suhu kamar tanpa mengalami peruraian. Penelitian ini bertujuan untuk memperoleh suhu dan volume air yang terbaik pada penyulingan minyak atsiri tipe uap dan air pada tanaman sirih hijau (Piper betle L.). Penelitian ini menggunakan metode perancangan percobaan Rancang Acak Lengkap 2 faktor yang terdiri dari 3 taraf dengan 3 kali ulangan yaitu suhu pemanasan dengan suhu 94˚C, suhu 98˚C, suhu 102˚C dan volume air 30 liter, volume air 35 liter, volume air 40 liter. Parameter yang diamati meliputi rendemen, kelarutan dalam alkohol dan warna. Dari hasil penelitian diperoleh rata-rata rendemen minyak terbaik dari kombinasi perlakuan suhu 98˚C dengan volume air 40 liter yaitu 0,143%. Warna minyak sirih kuning-merah dan kelarutan dalam alkohol 90% 1:1,9.   Kata Kunci: Piper betle, Minyak Atsiri, Rendemen.